A study on English proverbs denoting money with reference to the Vietnamese equivalents. / Nguyễn Thị Nga; NHDKH Asso. Prof. Le Van Thanh - Nguyễn, Thị Nga
The study deals with English proverbs denoting money with reference to the Vietnamese equivalents. The objectives of study are tofind out the similarities and differences between the English proverbs denoting money and Vietnamese ones in structural and semantic feature; and to provide some possible implications for teaching the English proverbs denoting money to Vietnamese learners of English as a foreign language. The data are taken collected from many sourcesrelated to proverbs denoting money to find out the similarities and differences in English and Vietnamese proverbs denoting money. This research is conducted by using descriptive method and comparative method. The result of the study shows that both English and Vietnamese proverbs denoting money use noun phrases, simple sentences, compound sentences, complex sentences.Vietnamese proverbs denoting money have compound sentences and complex sentences as main structures. English and Vietnamese cultures have effect on the semantic features of money proverbs. The study will become a useful tool for teachers of English to teach the culture to avoid misunderstanding